Evaluasi Kesejahteraan Rumah Tangga Nelayan melalui Indikator Peendapatan dan Pengeluaran (Studi Kasus di Desa Patoameme Kecamatan Botumoito Kabupaten Boalemo) - Verentiyansyah Duna; Supriyo Imran; Yuliana Bakari (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
This study aims to: 1) Analyze the income of fishermen's households in Patoameme Village, Botumoito District, Boalemo Regency, and 2) Determine the level of welfare of fishermen's households in Patoameme Village, Botumoito District, Boalemo Regency. The study was conducted in Patoameme Village, Botumoito District, Boalemo Regency, from December 2022 to February 2023. Patoameme Village was chosen as the location because many people there earn their livelihoods from fishing. The population in this study was all fishermen in Patoameme Village, Botumoito District, totaling 123 people. Sampling was carried out using the Simple Random Sampling method (SRS) with the Slovin formula, yielding a sample of 55 respondents. This study used data collection methods including observation, interviews, and documentation. The data analysis used is the analysis of income and household income, and the analysis of household welfare levels, using the criteria indicators according to Sayogyo in 1997, related to household expenditure and per capita expenditure per year. The results of the study showed that 1) The income of fishermen's households in Patoameme Village, Botumoito District, Boalemo Regency averaged Rp. 78,322,446/year from fishing businesses, an average of Rp. 71,122,446/year and from non-fishery business income, an average of Rp. 7,200,000. 2) The level of welfare of fishermen's households in Patoameme Village, according to the Sayogyo (1997) criteria indicators, is included in the Non-Poor Family indicator.